PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM KAITANNYA DENGAN NILAI SISWA DI SMK NEGERI 1 LAMONGAN - Maharani Zunan N, (Pendidikan Ekonomi, 2010)
Teachers as facilitators in learning process are expected to have the ability to use jigsaw method. Jigsaw is a learning model in which students work in groups, each of which consists of 5 to 6 students of hetarogenous backgrounds. The study is intended to know the implementation of jigsaw learning in SMK Negeri I Lamongan and the students response towards to the use of the jigsaw model. The classroom action research concisted of 3 cycles. The average scores gained from pre test I-III were 64.6, 73.3, and 80.3 respectively, whereas the average scores in posttest were 73.1, 82.6, 88.3 respectively. It means that the students scores increase. Thus, the implementation of jigsaw model in SMKN I Lamongan ran well.